Common factors in the presentation and management of chronic temporomandibular disorders and chronic overlapping pain disorders. (7th July 2020) - McCloy, Karen; Peck, Christopher; Farah, Camile S.; Balasubramaniam, Ramesh
Abstract: The International Association for the Study of Pain has released a new classification scheme for chronic pain. This classification scheme describes chronic pain as either a symptom of a disease (chronic secondary pain) or the disease itself (chronic primary pain). Chronic temporomandibular disorders have many similarities to other proposed chronic overlapping pain disorders, but are classified and managed by dental practitioners as a localized pain condition of the orofacial region. We review the literature to describe the similarities between chronic temporomandibular disorders and chronic overlapping pain disorders, and discuss how this evolving concept may affect the way that dentists approach the diagnosis and management of chronic temporomandibular disorders.